Decrease in the Number of Patients Presenting With ST-Segment Elevation Myocardial Infarction Across Catheterization Centers in Indonesia During the Coronavirus Disease 2019 Pandemic - Firman, Doni; Mangkuanom, Arwin Saleh; Iryuza, Nanda; Fahri, Ismir; Artha, I Made Junior Rina; Mulia, Erwin; Syukri, Muhammad; Yonas, Emir; Pranata, Raymond; Alkatiri, Amir Aziz (Frontiers in Cardiovascular Medicine, 2021)
Background The coronavirus disease 2019 (COVID-19) pandemic has become a global problem, put a heavy burden on the health care system, and resulted in many fatalities across the globe. A reduction in the number of cardiac emergencies, especially ST-segment elevation myocardial infarction (STEMI), is observed worldwide. In this study, we aimed to analyze the trends of cases and presentation of STEMI across several cardiac catheterization centers in Indonesia. Method This retrospective study was performed by combining medical record data from five different hospitals in Indonesia. We compared data from the time period between February to June 2019 with those between February and June 2020. Patients who were diagnosed with STEMI and underwent primary percutaneous coronary intervention (PPCI) procedures were included in the study. Results There were 41,396 emergency department visits in 2019 compared with 29,542 in 2020. The number of patients with STEMI declined significantly from 338 in 2019 to 190 in 2020. Moreover, the total number of PPCI procedures reduced from 217 in 2019 to 110 in 2020. The proportion of PPCI was not significantly reduced (64.2% vs 57.9%). The majority of the patients were men, with a mean age of 54 years in 2019 and 55 years in 2020. We observed a significantly longer door-to-balloon time in 2020 than in 2019 (p<0.001). We also observed a difference in the door-to-balloon time and ischemic time between the two periods. Conclusion We observed a decline in the number of patients presenting with STEMI to our centers. However, we observed no significant decline in the percentage of PPCI performed across our centers during this pandemic.